Troponin T and C-reactive protein levels in patients with unstable angina pectoris - Karaca, I; Ilkay, E; Ilhan, F; Akbulut, H; Akbulut, M; Arslan, N (Medimond S R L, 2001)
Positivity of cTnT in clinical course of UAP manifests that risk cardiac event is high in acute and early follow up periods. CRP is an important indicator of plaque inflammation. It's closely related with long period prognosis of acute coronary syndromes. Purpose of the study was demonstrate the role of inflammation in cTnT positive and negative UAP patients by CRP levels. In 65 patients diagnosed as UAP cTnT in 2-6-12-18 and 24th hours was measured. In the study. cTnT higher than 0.1 mug/L was regarded as positive, if lower as negative. In blood specimens taken from all patients 48-72 hours later CRP was measured. CRP level in cTnT positive group (n=23) was 43.18 (% 95 CI, 20, 42-65, 95); in cTnT negative group (n=42) was 13.28 (% 95 CI, 7,18-19, 32). There was correlation between cTnT positivity and CRP levels in spearman correlation analysis (r=0.524, p<0.01).
4th International Congress on Coronary Artery Disease -- OCT 21-24, 2001 -- PRAGUE, CZECH REPUBLIC
Keywords: Prognostic Value; Inflammation; Risk; Disease